Validation of the Educational Game Media "Hurufia" in Recognizing Letters for Children Aged 4-5 Years - Karisma Ainurosida; Risma Nugrahani (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
The ability to recognize letters is an important aspect in the development of early childhood literacy that needs to be stimulated through interesting learning activities that are appropriate to the child's characteristics. Based on the results of observations at Dharma Wanita Jegulo 3 Kindergarten, it was found that out of 10 children aged 4–5 years, 5 children still had difficulty in recognizing letters. This study aims to determine the level of validity of the educational game media HURUFIA (Children's Interactive Letters) based on Canva AI in introducing letters to children aged 4–5 years. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of two material experts, two media experts, one class teacher, and 10 children aged 4–5 years at Dharma Wanita Jegulo 3 Kindergarten. Data collection techniques used material expert validation questionnaires, media expert validation questionnaires, and teacher response questionnaires. Data were analyzed using quantitative descriptive techniques by calculating the percentage of media feasibility. The results of the study showed that the HURUFIA educational game media obtained a validation percentage of 75% from material experts with a category of feasible and 90% from media experts with a very feasible category. In addition, teacher responses to the media obtained a percentage of 83.5% with a very feasible category. These results indicate that the HURUFIA educational game media based on Canva AI is suitable for use as a learning medium to introduce letters to children aged 4–5 years. Thus, HURUFIA media can be an alternative learning media that is innovative, interactive, and appropriate to the characteristics of early childhood in supporting early literacy development.